THE EFFECTIVENESS OF USING PARTICIPATION POINT SYSTEM (PPS) METHOD IN TEACHING ENGLISH AT THE ELEVENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 9 MAKASSAR - Nilam Cahya Kasman; Andi Tenri Ampa; Farisha Andi Baso (FKIP Unismuh Makassar, 2021)
Productive skill is one of types language skills. It is also known as active skill because it covers writing and speaking skill. Learners need to generate language to express their ideas either in speech or text. This research aimed at finding out the improvement of the students’ writing and speaking skill through Participation Point System (PPS) Method in teaching English. The researcher used pre-experimental design. The sample consisted of 20 students which was taken by using total sampling technique. The research findings showed that the students’ mean score in writing skill in terms of content was 48.30 pre-test to be 78.25 in post-test with 62.00% improvement. Then, the mean score in terms of organization was 45.80 pre-test to be 78.25 in post-test with 70.85% improvement. Meanwhile the students’ mean score in speaking skill in terms of pronunciation was 43.30 pre-test to be 67.55 in post-test with 47.23% improvement. and organization in post-test was higher than pre-test. Then, the students’ mean score in speaking skill in terms of pronunciation and vocabulary in post-test was higher than pre-test. The t-test analysis also showed that Sig.2-tailed = 0.005 which is smaller than α = 0.05. It means that there was a significant difference of students’ writing and speaking skill before and after using Participation Point System (PPS) Method. Based on the finding, it can be concluded that Participation Point System (PPS) Method was effective to improve students’ skill in teaching English at the eleventh grade students of SMA Muhammadiyah 9 Makassar.